NetGeneREGION Filipino youth's manifestation of regionalism in social networking sites - Carabeo, Diane Marie Bugay; Cipriano, Roxanne Girlie B. (2012)
"This thesis examines how provincial college students in Metro Manila manage and negotiate their offline and online regional identities. The researchers saw the need for this study after finding a bulk of foreign literature showing college students' use of SNS migrate their offline behavior such as maintenance of networks and projection of self-image. To explain this phenomenon, the researchers used Tajfel and Turne's Social Identity Theory (SIT) which asserts that the individual manages and negotiates his identity, so that it reflects his group, to achieve high self-esteem. This cross-sectional, descriptive study employed both quantitative and qualitative data gathering methods. It analyzed the provincial college students' profile construction offline and online based on their communication behaviors. Five (5) sets of focus group discussions were conducted to know the offline regional behavior of the informants. A content analysis of the informants' social networking sites was conducted to study how they selectively display information about their regional identity. The informants were classified based on their projection of regional identity using an adaptation of Phinney's (1989) typologies of ethnicism - Diffused, Foreclosed, Moratorium, Achieved-Endorsed, Achieved-Unendorsed. The study shows that even though the provincial students have respective types of regionalism, they do not manifest this online because they utilize SNS for various reasons other than promotion of regional identity."
Vita.
Undergraduate thesis (A.B. Communication Research)--University of the Philippines, Diliman.
Keywords: Oneline social networks -- Philippines